2013
DOI: 10.1007/s00228-013-1606-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of lamotrigine in paediatric and young adult epileptic patients—nonlinear mixed effects modelling approach

Abstract: The LTG population pharmacokinetic model developed in this study may be a reliable method for individualising the LTG dosing regimen in paediatric and young adult patients on combination therapy during therapeutic drug monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…On the other hand, LTG CL in patients concomitantly treated with inducers of hepatic metabolism (carbamazepine, phenytoin and phenobarbital) was 55% higher. This is consistent with the previous reports . The current guidelines for LTG dosing account for the clearance alteration in patients when using enzyme inducing or inhibiting drugs .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, LTG CL in patients concomitantly treated with inducers of hepatic metabolism (carbamazepine, phenytoin and phenobarbital) was 55% higher. This is consistent with the previous reports . The current guidelines for LTG dosing account for the clearance alteration in patients when using enzyme inducing or inhibiting drugs .…”
Section: Discussionsupporting
confidence: 92%
“…We confirmed that LTG CL and V depended on patient's body weight. Similar results have been reported by other authors in paediatric and adult populations of epileptic patients . In accordance with the allometric scaling approach the effect of weight on V was more adequately described with the linear model, while a power model was more appropriate for the relationship of weight with CL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…LTG exhibits first-order linear pharmacokinetics with rapid and complete absorption when administered orally and is bio-transformed mainly through uridine diphosphate glucuronosyltransferase (UGT) (Chan et al, 2001), whose metabolism is significantly influenced by patient comedications. The co-administration of enzyme inhibitors [such as valproic acid (VPA) (Rivas et al, 2008; Brzakovic et al, 2014; Zhang et al, 2017; van Dijkman et al, 2018)] prolongs the LTG half-life by two-fold (van Dijkman et al, 2018), whereas the half-life is substantially shortened by coadministration of enzyme inducers [such as phenytoin (PHT) (Rivas et al, 2008; Brzakovic et al, 2014; Milosheska et al, 2016; Zhang et al, 2017; van Dijkman et al, 2018)].…”
Section: Introductionmentioning
confidence: 99%
“…The absorption was modelled as a zero‐order process following a short delay, reflecting the in vitro dissolution profile. The disposition was one compartment distribution with first‐order elimination, based on extensive previous experience . Other structure models, and a range of between‐subject variability and residual models were explored and found less suitable.…”
Section: Methodsmentioning
confidence: 99%